MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATERI BANGUN RUANG SISI LENGKUNG MELALUI MODEL PEMBELAJARAN REALISTICS MATHEMATIC EDUCATION (RME) PADA SISWA SMP NEGERI 5 TARAKAN - Supardji Supardji (Mathematics Education And Application Journal (META), 2020)
AbstractThis study aims to improve activities and mathematics learning outcomes using the Realistic Mathematics Educations (RME) learning model. The research was conducted in 3 cycles, each cycle consisting of planning, action, observation, reflection stages. While the learning approach in this study uses the Realistic Mathematics Educations (RME) learning model. The criteria for the success of this action research, the writer determines as follows: Students are declared successful in the learning that researchers do if: (1) The test score reaches ≥ 75 (KKM = 75), (2) The affective value of the observations on the learning process reaches ≥ 13. From the results of the study, it is illustrated that students get a written test score of ≥ 75 in cycle I as many as 19 students (59.38%), cycle II as many as 27 students (84.38%) and cycle III as many as 30 students (93.75%). From the observation results, it was found that there was an increase in student activity in learning, namely in the first cycle, 12 students (37.50%) who were active and very active, 21 students (65.63%) in cycle II and 25 students (78.13%) in the third cycle. ). Thus learning the curved side of the building material with the application of the Realistic Mathematics Educations (RME) learning model can improve learning outcomes of students at SMP Negeri 5 Tarakan by increasing learning outcomes from cycle I to cycle III, the results are significantly increased, in other words, children with learning difficulties. decreases, whereas from the results of observations obtained by increased activity, students are actively involved in the learning process and are able to spur students to learn to construct their own subject matter being studied and when experiencing difficulties students are assisted by their group friends who first understand the material being studied and if in a group no one can solve the difficulties faced directly ask the teacher.Keywords: Build curved side spaces, Realistics Mathematic Education (RME)AbstrakPenelitian ini bertujuan untuk meningkatkan aktifitas dan hasil belajar matematika dengan menggunakan model pembelajaran Realistic Mathematics Educations( RME). Penelitian dilaksanakan dalam 3 siklus, masing-masing siklus terdiri atas tahap Perencanaan, Tindakan, Pengamatan, Refleksi. Sedangkan pendekatan pembelajaran dalam penelitian ini menggunakan model pembelajaran Realistic Mathematics Educations (RME). Kriteria keberhasilan penelitian tindakan ini penulis tentukan sebagai berikut: Siswa dinyatakan berhasil dalam pembelajaran yang peneliti lakukan jika: (1) Nilai hasil test mencapai ≥ 75  (KKM=75), (2) Nilai afektif dari hasil observasi terhadap proses pembelajaran mencapai ≥ 13.Dari hasil penelitian diperoleh gambaran, siswa memperoleh  nilai hasil tes tulis ≥ 75 pada siklus I sebanyak 19 siswa (59,38%), siklus II sebanyak27 siswa (84,38%) dan siklus III sebanyak 30 siswa (93,75%). Dari hasil observasi diperoleh gambaran adanya peningkatan aktivitas siswa dalam pembelajaran yaitu pada siklus I, siswa yang aktif dan sangat aktifsebanyak 12 siswa (37.50%), siklus II sebanyak21 siswa (65,63%) dan siklus III sebanyak 25 siswa (78,13%). Dengan demikian pembelajaran materi bangun ruang sisi lengkung dengan penerapan model pembelajaran Realistic Mathematics Educations (RME) dapat meningkatkan hasil belajar siswa SMP Negeri 5 Tarakan dengan meningkatnya hasil belajar dari siklus I sampai dengan siklus III hasilnya meningkat secara signifikan dengan kata lain anak yang mengalami kesulitan belajar berkurang, sedangkan dari hasil observasi yang diperoleh peningkatan aktivitas, siswa terlibat aktif dalam proses pembelajaran serta mampu memacu siswa untuk belajar mengkonstruksi sendiri materi pelajaran yang sedang dipelajari dan bila mengalami kesulitan siswa dibantu teman sekelompoknya yang terlebih dahulu memahami materi yang dipelajari dan bila dalam suatu kelompok tidak ada yang bisa menyelesaikan kesulitan yang dihadapi langsung bertanya pada guru.Kata kunci: Bangun ruang sisi lengkung, Realistics Mathematic Education (RME)